Analisis Pengaruh Pendapatan Kontribusi Di Era Pandemi Covid-19 Terhadap Laba Perusahaan Asuransi Jiwa Syariah - Qurrotu Aini; Ria Rahmawati (Syar'Insurance: Jurnal Asuransi Syariah, 2023)
The Covid-19 pandemic has an impact on all industrial sectors. One of them is the sharia insurance company industry in Indonesia. With the existence of Covid-19, this has affected the profits of sharia life insurance companies. Therefore, this study will discuss one of the factors that can affect company profits, namely the contribution of income. In this study, regression analysis was used using the classical assumption test, hypothesis testing, t (partial) test, correlation coefficient test, and coefficient of determination test. From the simulation results, it was obtained that the revenue contribution only explained an effect of 4.4%, this meant that there were other factors that affected company profits during the Covid-19 pandemic era.